2014
DOI: 10.3126/eco.v20i0.11472
|View full text |Cite
|
Sign up to set email alerts
|

Forest Structure and Regeneration Pattern of Betula Utilis D. Don in Manaslu Conservation Area, Nepal

Abstract: Forest structure and regeneration of Betula utilis (D. Don) was studied in birch forest located in Samagaun valley (3500 -4000 m) of Manaslu Conservation Area. Vegetation sampling was done by quadrat method. Altogether 40 quadrats were sampled to determine the Importance Value Index (IVI) of tree species, and distribution pattern of seedlings and saplings. Regeneration was assessed by density -diameter curve. Four tree species were recorded from the forest. Betula utilis was the dominant tree species with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…The total sapling density of all tree species was higher than seedling density which is not a normal demographic development. Similar trend was also observed by Gaire et al 2010 at Langtang andSujakhu (2013) at Samagoan. There is a positive relationship between total basal area and seedling and sapling ( Fig.…”
Section: Fig 4 Tree Density Of Rhododendron Campanulatum (Rc) and Bsupporting
confidence: 88%
See 1 more Smart Citation
“…The total sapling density of all tree species was higher than seedling density which is not a normal demographic development. Similar trend was also observed by Gaire et al 2010 at Langtang andSujakhu (2013) at Samagoan. There is a positive relationship between total basal area and seedling and sapling ( Fig.…”
Section: Fig 4 Tree Density Of Rhododendron Campanulatum (Rc) and Bsupporting
confidence: 88%
“…Liang et al (2014) reported that the growth of Betula at the upper timberlines is limited by moisture. Sujakhu (2013) also emphasized that the current environment conditions were not favourable for the establishment of B. utilis seedlings. Moisture and deep shade might be detrimental for seedling establishment.…”
Section: Fig 4 Tree Density Of Rhododendron Campanulatum (Rc) and Bmentioning
confidence: 99%
“…The tree, sapling and seedling density of A. spectabilis recorded in this study is comparable with the density in the other parts of the Nepal Himalaya. A. spectabilis sapling density was 648 stems/ha in Manaslu Conservation Area (Sujakhu et al, 2013) and the sapling density declined with increase in elevation. In the same area, A. spectabilis tree density is 412 stem/ha and basal area is 11.64 m 2 /ha.…”
Section: Population Structure Of a Spectabilismentioning
confidence: 95%
“…In the same area, A. spectabilis tree density is 412 stem/ha and basal area is 11.64 m 2 /ha. The total tree density was more in the mixed forest (2,054 stems/ha) than in the pure forest (1,707 stems/ha) (Sujakhu et al, 2013). Kunwar and Sharma (2004) found out A. spectabilis density ranged from 250 to 510 trees/ha in Amaldapani and Juphal community forests of Dolpa District.…”
Section: Population Structure Of a Spectabilismentioning
confidence: 95%
See 1 more Smart Citation